2020
DOI: 10.4103/jehp.jehp_589_20
|View full text |Cite
|
Sign up to set email alerts
|

Fear and rumor associated with COVID-19 among Iranian adults, 2020

Abstract: CONTEXT: At time of epidemics, fear and rumors in the community are the main obstacles to the success of prevention programs. AIMS: The aim of the study was to investigate the fear and rumors of coronavirus disease 2019 (COVID-19) among the Iranian population. SETTINGS AND DESIGN: This nationwide cross-sectional study was conducted on residents of six cities of Iran via street-based multistage sampling in March 2020. SUBJECTS A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
(17 reference statements)
2
5
0
Order By: Relevance
“…They are believed not to assist people's coping during crisis and tended to stir up negative emotions during the pandemic. These results were consistent with recent findings, which found that rumours trigger negative outcomes, such as increasing fear (Zamanian et al, 2020) and leading to violence (Greenhill & Oppenheim, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…They are believed not to assist people's coping during crisis and tended to stir up negative emotions during the pandemic. These results were consistent with recent findings, which found that rumours trigger negative outcomes, such as increasing fear (Zamanian et al, 2020) and leading to violence (Greenhill & Oppenheim, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Our result also suggested that patients with college education experience had a higher level of FoP than patients with primary education experience, which is different from the studies of Zheng Hu and Meissner et al [ 31 , 32 ]. Consistent with us, the higher the educational level, the more fear of coronavirus disease 2019 [ 33 ]. Patients with high education level are more willing to learn disease-related knowledge.…”
Section: Discussionsupporting
confidence: 64%
“…[ 2 32 33 ] Our findings mirror the results from previous coronaviruses outbreak studies, where the psychiatric morbidities ranged from 10% to 35% even in the postillness stage. [ 34 ] Mazza et al . also reported high rates of PTSD, depression, anxiety, insomnia, and OC symptomatology in a sample of COVID-19 survivors, thus corroborating with our study results.…”
Section: Discussionmentioning
confidence: 99%